Analisis Penguasaan Produksi Garam PT Garam (PERSERO) berdasarkan Prespektif Ketentuan Pengecualian - Mochamad Cholil; Rhido Jusmadi (Jurnal Persaingan Usaha, 2023)
Garam (Persero) is the only State-Owned Enterprise engaded in the oldest salt production and marketing industry in Republic of Indonesia. The existence of PT. Garam (Persero) as a business actor is suspected to dominate the national salt production. This becomes interesting to investigate because one form of action that can result in monopolistic practices and/or unfair business competition is control over the production and/or marketing of goods and/or services. Therefore, this research was conducted to determine the basic authority possessed by PT. Garam (Persero) in controlling salt production in Republic of Indonesia and analyzing whether the control of salt production carried out by PT. Garam (Persero) is a form of practice that is excluded or not in the provisions of Article 50 and Article 51 of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practis and Unfair Business Competition. The research method used is the legal research. The approach taken is the statute approach. The results showed that PT. Garam (Persero) in controlling salt production in Republic of Indonesia has absolutely no basis of authority. In addition, the control of salt production carried out by PT. Garam (Persero) is a form of practice that is not excluded from the provisions of Article 50 and Article 51 of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practis and Unfair Business Competition. Keywords: PT. Garam (Persero); control; salt